EFFECTS OF DIFFERENT DOSES OF GLYCINE BETAINE AND TIME OF SPRAY APPLICATION ON YIELD OF COTTON (GOSSYPIUM HIRSUTUM L.) - Makhdum, Muhammad Iqbal; Shababuddin, (Journal of Research (Science), 2006)
A field study was conducted with objectives to determine the effects of different application rates of glycine betaine and time of application in field grown cotton at Central Cotton Research Institute, Multan. Four levels of glycine betaine (0.0, 1.0, 3.0 and 6.0 kg ha-l) were applied exogenously at three physiological growth stages, i.e., at squaring, first flower and peak flowering. Cotton cultivar CIM-448 was used as test crop. Results showed that different doses of glycine betaine and its foliar application at various growth stages showed significant differences in seed cotton yield, number of bolls per plant and boll weight. The highest seed cotton yield was obtained by the foliar application of 3.0 kg ha-l glycine betaine at squaring phase. The value of seed cotton yield ranged from 1956 to 2464 kg ha-l in various treatments.